Mahatma Gandhi (1869-1948). An Inquiry into Adult Education, Teacher Training, Vocational Education, and Women's Education - Kariman Mahmoud (Adult Education Research Conference, 2024)
Despite Gandhi’s contributions to education, little research has explored his accomplishments in adult education. This paper sheds light on Gandhi's reflections on adult education, teachers' training, vocational, and women's education.
Keywords: Gandhi; adult education; teacher training; vocational education; women' s education